Comparative Study of the Electrical Parameters of Individual Solar Cells in a c-Si Module Extracted Using Indoor and Outdoor Electroluminescence Imaging - Amit Singh Rajput (IEEE Journal of Photovoltaics, 2020)
10.1109/JPHOTOV.2020.3001720